The Theoretical Background of Application of Projective Methods in Experimental Studies - Avanesyan, Hrant (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
Currently, as usual, there are unsolved questions about the problem of the theoretical and methodological basis of "projective psychology", about its conceptual principles. The article reveals several issues about the principles on which the classification of projective techniques is based, what are their advantages and disadvantages and modern criteria of interpretation and combination with other methods. The main assumption is due to the fact that in the process of experimental studies projective techniques are not appropriate to apply separately to standardized psychometric methods and their relevance depends on psychodiagnostic value, i.e. there is a possibility for a more integrated description and identify of person’s unconscious patterns.